Prognostic Correlation of Basic Fibroblast Growth Factor and Vascular Endothelial Growth Factor with Radiological Tumor Size in Pediatric Nephroblastoma and Neuroblastoma: A Prospective Study - Pujana Kanneganti; Basant Kumar; Priya Mathew; Vikas Agarwal; Rajanikant Yadav; Ankur Mandelia; Vijai Datta Upadhyay (Journal of Indian Association of Pediatric Surgeons)
Introduction: Angiogenesis plays an important role in the growth, progression, and metastasis of solid tumors. Basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF); both are potent angiogenic factors implicated with the growth and metastasis of solid tumors mostly in adult studies. Rapidly growing and large-size tumors have a positive correlation with these factors which are measured in serum and urine samples of patients. There is little literature available for pediatric patients that compare the computed tomography findings (size) of pediatric solid tumors with serum VEGF and serum/urinary bFGF. This prospective study aims to determine the correlation of serum VEGF and serum/urinary bFGF with the size of common pediatric solid tumors (nephroblastoma and neuroblastoma [NB]) to determine its diagnostic and prognostic significance. Materials and Methods: A prospective case–control study was done for 3 years (December 2020 to November 2023) at our institute. All children aged 1 day to 18 years admitted with the diagnosis of NB and nephroblastoma (Wilms’ tumor [WT]) were included after parental consent. The control group includes children of varying ages without any malignancy. Blood and urinary samples were collected at admission before or a week after the biopsy and the level of bFGF and VEGF was analyzed with the ELISA method. Triple-phase computed tomographies along with recommended evaluation were performed according to the tumor as per international standard protocols. Appropriate statistical analyses were done. Results: A total of 30 patients were included in the cohort, of which 13 patients were with the diagnosis of WT. Only 7 patients had metastatic disease. All the patients were treated with neoadjuvant chemotherapy, surgery, and radiotherapy according to their presentation and tumor stage. Both the growth factors, i.e., VEGF (median value - 314.38 pg/mL) and bFGF (median value - 18.96 pg/mL), are elevated in all the tumor patients in comparison with the controls (median VEGF - 100.51 pg/mL and bFGF - 15.6 pg/mL). When compared with the tumor size, no significant associations are found (with VEGF P - 0.40 and with bFGF P - 0.44). Conclusion: Although no satistically significant correlations were found between serum/urinary levels of bFGF and VEGF with tumor size, this study showed the raised median serum value of bFGF and VEGF in patients with NB and WT in comparison to controls and provided the rationale to explore this issue on a larger group of patients.